Constitution of India: popular sovereignty and democratic transformations - Sen, Sarbani (Delhi, 2007)
The first book to explore the relationship between constitutionalism and popular sovereignty in the Indian context. It argues that the identity of the Indian constitution was shaped by a period of prolonged popular engagement in resisting a colonial regime and that it can be seen as a political symbol of national identity.
Keywords: Constitution-India